Institutional Economics and the American Trade Union Movement - Barkin, Solomon (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1988)
In the context of the major changes of the eighties, the author examines how institutional economists and unions can be of great assistance one to the another.